"Desarrollo de un sistema informático de apoyo a la elaboración de los distributivos académicos de la Universidad Técnica Estatal de Quevedo - Cocha Yanchapaxi, Rolando Gabriel (2014)
The main objective of this thesis is the proposal of a Management Model Development processes Distributivos Academicos of Universidad técnica Estatal de Quevedo in the opportunity to convert as advantages in academic, administrative and budgetary knowledge contained unique the people involved and other factors identified in a competitive advantage that will serve as an opportunity for the institution to keep on growing in the innovative aspect. The Distributive multicomponent feed prior to its formation, these components range from the curricula and pensums legally approved planning through parallel courses and careers, to institutional needs regarding management activities. This thesis has been developed according to the guidelines of exploratory research, and therefore, the main source of primary information are interviews with the people involved acquired by observation, especially compared to the way the current process with those developed these processes are performed manually, but, we hope that by the beginning of the academic period of 2014 and beyond, the UTEQ have its own computer system for the development of their Distributive Scholars.